2019
DOI: 10.14569/ijacsa.2019.0100431
|View full text |Cite
|
Sign up to set email alerts
|

ABCVS: An Artificial Bee Colony for Generating Variable T-Way Test Sets

Abstract: To achieve acceptable quality and performance of any software product, it is crucial to assess various software components in the application. There exist various softwaretesting techniques such as combinatorial testing and covering array. However, problems such as t-way combinatorial explosion is still challenging in any combinatorial testing strategy, as it takes into consideration the entire combinations of input variables. Therefore, to overcome this problem, several optimizations and metaheuristic strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…However, all these approaches share a common factor: these approaches exploit the power of random combinatorial searching when they are integrated with heuristics for determining the t-strength covering array. The formulation of the optimization problem calls for an emphasis on two aspects: the devising of the objective function and the selection of the approach employing a pure-based approach [12] or hybrid-based approach [13]. In terms of the objective function formulation, some models use a minimization formulation, while others use a maximization formulation.…”
Section: A Csst Testingmentioning
confidence: 99%
See 2 more Smart Citations
“…However, all these approaches share a common factor: these approaches exploit the power of random combinatorial searching when they are integrated with heuristics for determining the t-strength covering array. The formulation of the optimization problem calls for an emphasis on two aspects: the devising of the objective function and the selection of the approach employing a pure-based approach [12] or hybrid-based approach [13]. In terms of the objective function formulation, some models use a minimization formulation, while others use a maximization formulation.…”
Section: A Csst Testingmentioning
confidence: 99%
“…The computational comparison between the firefly meta-heuristic algorithm, genetic algorithm, and ant colony optimization revealed that the firefly algorithm has a shorter optimization time. Other models developed for solving combinatorial software testing using meta-heuristic searching include the memetic algorithm (MA) in [19], the particle swarm optimization (PSO) in [20], the artificial bee colony (ABC) and corresponding developed variants in [13], [21]- [26], the harmony search algorithm (HSA) in [27], the bat algorithm (BA) in [12], [28]- [30], and the flower pollination algorithm (FPA) in [31] and [32]. All these models are considered pure models because they utilize a common pure meta-heuristic approach.…”
Section: A Csst Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, many heuristic and metaheuristic algorithms were used to solve many optimization problems; such as Minimum Vertex Cover Problem (MVCP), Traveling Salesman Problem (TSP), 15 puzzle problem, task scheduling, software testing, and non-optimization problems [1][2][3][4]. Examples of heuristic algorithms are A* heuristic search algorithm and iterative deepening A* (IDA*) heuristic search algorithm [5].…”
Section: Introductionmentioning
confidence: 99%
“…Equation 2is used to calculate these probabilities [25]. (2) where g a and g b are any competed groups, k is a constant and is the normalized size of g a 's solutions sizes that is calculated as in (3) [25]. 3On the consequence of the winner group determination, the vertices values of g i solution are updated using either the equation in line 24 or in line 26 [25].…”
mentioning
confidence: 99%